Non-Proxy Reductions of Eternalist Discourse - Correia, Fabrice (My University, 2013)
Eternalists believe that there are past things and future things which are not present. In contrast, presentists hold that only present objects exist. In this chapter, I discuss presentist reductions of eternalist discourse which do not involve quantification over proxies—i.e. presentistically acceptable surrogates for merely past and merely future entities.